Societal Values and Sexual Morality among Adolescents in Nigeria - Lawal, Adenike O.; Akerele, E. O.; Akinhanmi, Y.O. Uthman -; Solana, O. L.; Yangomodou, O. D.; Lawal, J. B. (NIU Journal of Humanities, 2021)
Morality refers to the way people choose to live their lives according to a set of guidelines or principles that govern their decisions about right versus wrong, and good versus evil. This work is basically an evaluative study as the subject under review is a contemporary issue. Descriptive â€“ analytical approach method of data collection was adopted. Results from this study revealed that teens growing up in today's society are subjected to increased demands on their physical, mental, and emotional resources. This study therefore recommended that, awareness of public/private boundaries â€“ Children and adolescents should understand public and private boundaries regarding sex in their own specific cultures and thus be able to navigate through these boundaries. This study concluded that, children and adolescents must understand what sexual morality and sexual immorality is, and build a sound ethical system to guide their temperament, including ideas of duties, respect for others, both ethical and unethical behaviors. Keywords:  Adolescents, Challenges, Morality, Sexual-Perversity and Value System